Comparative study of independent learning of the eldest and youngest students at SMP Negeri 15 Padang - Nadisa Humaira; Asmidir Ilyas (Consilium, 2021)
Every child has a different position in the family, there are firstborn, middle, youngest, only children. Each child's personality is different, even twins have different characteristics from one another. Children are expected to have high independence, one of which is independence in learning. Children who have independence in learning can do work without help from others, even children develop strategies in learning, set target values to be achieved, and evaluate the results of tasks that have been done. In fact, most of the youngest children are not able to be independent in learning, and some of the oldest children are already able to learn independently. This research aims to: (1) describe the learning independence of the eldest child and the youngest child, (2) describe the difference in the level of learning independence of the eldest child and the youngest child. This research uses a quantitative approach with a comparative descriptive research type. The subjects of this study were the eighth-grade students of SMP Negeri 15 Padang with the status of the eldest and the youngest children of 2 siblings and 4 siblings, amounting to 40 first-born students and 40 youngest students. Collecting data using a Likert scale model questionnaire, data were analyzed using descriptive analysis techniques and different test techniques with the help of the SPSS program version 20.0. The results revealed: (1) the learning independence of the eldest child is in the independent category with an average percentage of an achievement score of 67.5%, (2) the learning independence of the youngest child is in the fairly independent category with an average percentage of an achievement score of 55%, ( 3) available difference in the level of learning independence of the firstborn and youngest child with Sig. (2-tailed) 0.000 ? 0.05.